2015
DOI: 10.1007/s00415-015-7831-3
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of hippocampal integrity for memory outcome after surgical treatment of mesial temporal lobe epilepsy

Abstract: Surgical treatment of unilateral mesial temporal lobe epilepsy (mTLE) particularly bears the risk of episodic memory decline. The present study investigates the role of the ipsilateral hippocampal integrity for postoperative change in material-specific memory performance. In 104 patients who had undergone epilepsy surgery for unilateral mTLE, we analyzed pre- to postoperative changes of verbal and figural memory as a function of segmental neuronal cell densities of the resected hippocampus (cornu ammonis, CA1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
25
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 55 publications
6
25
0
2
Order By: Relevance
“…Further decline in memory following temporal lobe surgery is reported to occur in up to 25%, with older patients being particularly vulnerable . A better‐preserved hippocampus has been shown to be predictive of greater postoperative decline in verbal memory function and more significant postoperative memory declines have been reported with ILAE type 2 HS or better preserved CA1 . In terms of quantitative confirmation of regional neuronal preservation in the present study, we identified a statistical association between MAP2 labeling only in the subiculum and naming decline at 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…Further decline in memory following temporal lobe surgery is reported to occur in up to 25%, with older patients being particularly vulnerable . A better‐preserved hippocampus has been shown to be predictive of greater postoperative decline in verbal memory function and more significant postoperative memory declines have been reported with ILAE type 2 HS or better preserved CA1 . In terms of quantitative confirmation of regional neuronal preservation in the present study, we identified a statistical association between MAP2 labeling only in the subiculum and naming decline at 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…Initial research has suggested that TLE patients with type 2 pathology have intact preoperative memory ability that is comparable to that of patients with nonlesional TLE and significantly better than performance of individuals with types 1 or 3 . Furthermore, some data suggest that type 2 pathology is overrepresented among patients with left TLE and intact word list learning scores; however, cases of type 2 with episodic memory deficiencies have also been documented . Further, there is evidence to suggest that overall degree of neuronal loss may be a more important factor in episodic memory performance than the pattern of cell loss or the hippocampal subregions within which neuronal loss occurs .…”
Section: Introductionmentioning
confidence: 99%
“…1 HS has long been associated with episodic memory impairments in patients with TLE as well as better prognosis for memory outcome following temporal lobectomy. 4,5 Although many studies over the years have examined the relationship between hippocampal cell loss/ density and memory ability, [6][7][8][9][10][11][12] little is known about episodic memory ability/outcomes as they pertain to the HS pathology subtypes outlined in the ILAE Consensus guidelines. 1 Initial research has suggested that TLE patients with type 2 pathology have intact preoperative memory ability that is comparable to that of patients with nonlesional TLE and significantly better than performance of individuals with types 1 or 3.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sin embargo, la intervención implica un riesgo de deterioro de la memoria, con efectos diferenciales en la memoria verbal y no verbal, en pacientes con ELTm izquierda o derecha respectivamente, siendo la memoria verbal la más vulnerable [3][4][5][6][7] . Por ello, previo a la cirugía, es necesario realizar una completa evaluación del paciente, que incluye una historia clínica detallada, y al menos, EEG, pruebas de neuroimagen (resonancia magnética [RM]) y una correcta evaluación cognitiva.…”
Section: Introductionunclassified